Reinforcement of cement mortar with recycled polyethylene waste for construction applications - Flomo, M.K.; Azeko, S.T.; Arthur, E.K.; Kukurah, J-D.; Mustapha, K.; Annan, E.; Agyei-Tuffour, B. (JOURNAL OF COMPOSI T E MATERIALS, 2021)
This current research work combines both experimental and theoretical study of the impact of cement mortar reinforced with recycled polyethylene waste for applications in the construction industry. The work explores incorporating low density polyethylene (LDPE) waste into cement mortar to improve its fracture toughness and flexural strength with balanced compressive strength. Different volume fractions (0, 5, 10, 15, 20, 30, and 40%) of the powdered LDPE were mixed with cement and the density, compressive strength, flexural strength, and the fracture toughness were observed under different testing conditions. All specimens were tested after curing of 7, 14, and 28 days. The results show that there was 6% increase in the fracture toughness at 5 vol. %, 7% increase at 10 vol. %, and 24% increases at 20 vol. % of LDPE. Also, it was observed that the weight and compressive strength decreased with increasing volume fraction up to 40 vol. % of LDPE waste. The results for the survival/failure probability show that the PE-mortar composites with PE volume percentages up to 20 vol. % had the highest survival probability. The composite with this volume percentage can withstand crack up to 6mm, with a survival probability of 0.6.
Research Article
Keywords: Polyethylene; survival/failure probability; brittle fracture modelling; mechanical testing; crack opening tip displacement